Evaluation of Students’ Chemistry Learning and Experiences in Collaborative Immersive Virtual Reality - Ungu, Dewi Ayu Kencana (Curtin University, 2024)
This study aims to understand how students utilise and perceive collaborative immersive virtual reality (iVR) to learn chemistry concepts, compared to magnetic models. Multimodal cross-case analysis revealed that undergraduate students appreciated learning complex spatial arrangements of molecules in iVR, but the extent of learning and engagement varied depending on prior knowledge and group composition. Evaluating the dynamics of students’ learning experiences can elucidate the unique educational benefits of iVR, revealing nuances that conventional evaluation overlooked.